Activity, Activity Personalization, and Well-Being in Nursing Home Residents With and Without Cognitive Impairment: An Integrative Review. Issue 5 (20th October 2022) - Shryock, Sarah Kelly; Meeks, Suzanne
ABSTRACT: Objectives: Engagement in personally relevant and pleasant activity is a facet of many theories of well-being. This integrated review and narrative synthesis explored the hypothesis that activity participation improves well-being for nursing home residents. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we searched MEDLINE, PsycINFO, Academic Search Complete, Psychology and Behavioral Sciences Collection, Embase, and CINAHL for research published between 2006 and 2018. We included peer-reviewed, English-language studies of nursing-home residents, with interventions focused on activities and on well-being or affect outcomes. Results: After screening, the search yielded 45 studies: 15 reviews of specific activities and 30 empirical articles. We found consistent support for tailored activity interventions and less consistent support for specific or generic activity interventions with the possible exception of music therapy. Research focused on specific activity types had methodological limitations and confounds with activity preferences. Conclusions: Participation in activities may improve well-being in residents of nursing homes. Tailored activities are likely to be superior to those provided indiscriminately to all residents. Clinical Implications: Improving quality of life in long-term care should include opportunities to engage in activities; those most effective will be tailored to individuals and no single activity will be effective for everyone.